Book of the nation’s alliance with the histories of the imams - Najm, Ibrahim Makhoul (Al-Adab Journal, 2015)
In the name of God the merciful-Thank God,prayer and peace be upon Mohammad the Messengr of God and the God of peace and his owners and recoginition of a lot,this manuscript its number(11577)in the Hadith at the door of House of Manuscripts of General organization for Antiguities ,dating to the twelfth century,the eighteenth-auther.Brand-sheikh –Suleiman bin Mohammad-aldagoukay-Alshafii.consists of twelve pages-I Achieving this manuscript its include dateto the life of imams of the four sects of sunnis community forward(imam Abu-Hanifah t(150 AH) and imam Malik Bin Anas t(179 AH) and imam Alshafii t(204 AH) and imam AHMaD Bin HAnbal t(241 AH)mercy of GoD).author balanced between beirths ,deaths,and contemporary each otherand what happened to them from the events and aptlaouat with princes and sultans who asrohm and the virtues of each of them and astatement and showed the manuscript to the imam ABU-Hanifa August narrated from imam MAliK novice ownerNboyen ,one in the provision of carcass and other provision in the marriage. I have been studied the hadith booss and showed the reprted error or the signed the author or the coptist, and in this manuscript statement for the life of three media scholars to talk of the prophet(imam Layth bin saadEgytion t(175 AH) and imam ALBukre t(256AH) and imam MUSLimibinAHaJJaJ t(261 AH)balanked between birth,death,and showed their knowledge and their works Alhadithip and capacity knowledge and virtues ,mercy God Almighty.Najim---profesor,DR at Islamic educion and holy Quran scienceIbraheemmakhoolReligion means ,preparation of teacher teaching institute Alrasafh first.The mercifulInthenameofAllah